2017
DOI: 10.1515/biol-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Thrombophilic Gene Mutations in Patients with Deep Vein Thrombosis and in Women with Recurrent Pregnancy Loss

Abstract: Thrombophilia may be anticipated by single or combined hereditary defects in encoding genes factor V, Prothrombin, and MTHFR. The aim of this study was to determine the prevalence and associated risks of V Leiden (G1691A), Prothrombin (G20210A), and MTHFR (C677T) mutations in Saudi women with Deep Vein Thrombosis (DVT) and women with recurrent pregnancy loss (RPL). Protein C and protein S activity were measured to determine combined effects, if any. We examined 60 women with a history of DVT and 60 with RPL, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(14 reference statements)
5
2
1
Order By: Relevance
“…However, it is not associated with MI; the two-tailed P value equals 0.5 in Libyans residing in Tripoli. These results are in agreement with other previously published studies in Netherlands [13,14], Pakistan [15], Tunisia and Lebanon [16], Saudi Arabia [17], US [18], Venzuela [19], and Denmark [20]. Regarding myocardial infarction, our results showed no association of FVL with MI.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is not associated with MI; the two-tailed P value equals 0.5 in Libyans residing in Tripoli. These results are in agreement with other previously published studies in Netherlands [13,14], Pakistan [15], Tunisia and Lebanon [16], Saudi Arabia [17], US [18], Venzuela [19], and Denmark [20]. Regarding myocardial infarction, our results showed no association of FVL with MI.…”
Section: Discussionsupporting
confidence: 93%
“…The prothrombin G20210A mutation of the prothrombin gene exhibits increased synthesis and functional capability of prothrombin, favoring thrombosis In this study, the frequency of the FVL G1691A heterozygous mutation (G/A) was 3.5%, whereas that of the homozygous mutation (A/A) was 0.5% [OR = 17.71, 95% confidence interval (9%% CI): = 1.015-309.05], which is consistent with the results of previous studies [17,18]. The rate of the FVL G1691A polymorphism is almost similar in various pregnancy-associated clinical manifestations [19]. In a group of Sudanese women with preeclampsia, the frequency of such polymorphism was found to be 9.6% [20].…”
Section: Discussionsupporting
confidence: 90%
“…In line with the results of the current work, it was found that the frequencies and the prevalence of the heterozygous FVL were4 (6.6%), but when prothrombin G20210A, and MTHFRC677T genotypes were taken into consideration, it was shown that they markedly differ from the outcomes of the present study, as they were recorded in Saudi patients with a prevalence of with RPL were 2 (3.3%), and 3 (5%), respectively (Elgari et al, 2017).Consistently, Kobashiet al, 2005 did not find the FV Leiden mutation in Japanese women with RPL (Kobashiet al, 2005) .Comparable to the results of the present study, it was stated that Tunisian women had higher prevalence of MTHFR 677T/T in late and early-late RPL (Mtiraoui et al, 2006) Moreover, other researchers did not find any association between prothrombin G20210A polymorphism and fetal losses after IVF. (Kutteh et al, 1998) On the other hand, Di Micco et al, (2008) reported that inherited thrombophilia and in particular the prothrombin A20210G variant is relevant risk factor for recurrent pregnancy loss and this observation clearly contradicts the findings of the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Thrombosis occurs as an outcome of a deviated function of the blood clotting system. Therefore, it is pivotal to determine the frequencies and risks of the most encountered genetic mutations causing deep vein thrombosis or recurrent pregnancy loss (Elgari et al, 2017). In recurrent pregnancy loss, there is much debate about cause and association.…”
Section: Discussionmentioning
confidence: 99%